Aspects and consequences of the Kingdom of England’s legislative regimes regarding the Hanseatic League, the Dutch Republic and Scotland - Haitas, Daniel (Pro Futuro, 2020)
A tanulmány évszázados áttekintést nyújt az Egyesült Királyság kereskedelmi kapcsolatait illetően a Hanza Szövetséggel, Hollandiával és részben Skóciával. A munka középpontjában azok a törvényi rendelkezések állnak – ideértve a monopóliumokat is –, amelyek alapvetően meghatározták az angol kapcsolatokat a 14–15. században a Hanza Szövetséggel, illetve a 17. században Hollandiával. Skócia kapcsán az 1707-ben kötött Unió vonatkozásában (Acts of Union) a kereskedelmi kapcsolatok történeti perspektívából való elemzésére törekszik a tanulmány, bízva abban, hogy az angol kereskedelmi kapcsolatok történelmi távlatból való elemzése napjainkban is hasznos lehet. The article surveys elements of the Kingdom of England’s relations with the Hanseatic League, the Dutch Republic and Scotland throughout certain periods of history. There is a particular focus on legal measures and regulations adopted by England with regards to the traders of the Hanseatic League in the 14th and 15th centuries and Dutch traders in the 17th century. In relation to Scotland, there is an overview of how restrictions enacted by England helped to contribute in part to the Union of 1707, and of some consequences which followed on from this important historical development. The study can be said to be of interest in terms of certain developments taking place in Europe at the present time.